Analisis Kinerja Ruas Jalan akibat Pengaruh On-Street Parking di Jalan Nani Wartabone I Kota Gorontalo - Fasya Aulia Azzahra Dama; Yuliyanti Kadir; Frice Lahmudin Desei (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
On-street parking often occurs due to limited parking spaces, especially in high-activity areas. Nani Wartabone 1 Street (formerly Pandjaitan Street) experiences significant side friction, particularly from parking activities, impacting road performance. This study evaluates the street’s performance under these conditions using field data collection and analysis based on the MKJI 1997 guidelines. Data were collected on Monday, Wednesday, and Saturday. Traffic flow recorded was 1,124 vehicles per hour on Monday, 1,146 vehicles per hour on Wednesday, and 1,341 vehicles per hour on Saturday. The degree of saturation (DS) due to on-street parking was 0.59, 0.56, and 0.52, respectively, placing the road service level in category C. Without on-street parking, the service level improved to category B, with DS values of 0.44, 0.41, and 0.39, respectively. These results indicate that on-street parking negatively affects road performance. The highest parking accumulation occurred between 8:00–9:00 PM on Saturday, June 15, 2024, reaching 130 vehicles per hour. The parking index exceeded 100% for cars, indicating insufficient parking space, while motorcycle parking remained fully occupied. These findings highlight the need for better parking management to improve traffic conditions on Nani Wartabone 1 Street.